Pengaruh Perendaman Plat Resin Akrilik Dalam Larutan Ekstrak Daun Pandan (Pandanus Amaryllifolius Roxb.) Terhadap Pertumbuhan Jamur Candida Albicans - Audira, Irine Ardensa, drg. Noor Hafida Widyastuti, Sp.KG, drg. Fitria Nur Malita Sari (2015)
Acrylic was used as basic material of removable denture. Acrylic resin was easy to form and non-toxic material. It also has aesthetic aspect. Micropore on its structure can attract fungus to attached, such as Candida albicans. Candida albicans can cause denture stomatitis. The plate should be submerged into disinfectant solution. Alternative herb can be used is pandan leaf. Pandan leaf contains antifungal such as flavonoids, alkaloid and saponin. The purpose of this study was to understand the effect of acrylic resin plate submersion into solution extract of pandan leaf against Candida albicans growth 24 of 10x10x1mm plates of acylic resin were used as sample divided into 6 treatment groups with 0,2 chlorhexidine as positive control, aquades as negative control and 10%, 20%, 40% , 80% concentration of pandan leaf. Samples were inoculated with Candida albicans for 24 hours then submerged into each treatment for 8 hours. Samples were then attached on vortex mixer in 1 minute and diluted up to 10-3. Germination was done on Sabouraud agar petri dish. These petri dishes were incubated for 48 hours at 370C, and then colonies of fungi were counted. The data were analyzed using Kruskal-Wallis and Mann-Whitney Test. The result showed that there was an effect of acrylic resin plate submersion into solution extract of pandan leaf againt Candida albicans growth, while the most effective concentration of the pandan leaf extract was 80%.